2008
DOI: 10.1021/ie8010337
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Acrylic, Propionic, and Butyric Acid Using Aliquat 336 in Oleyl Alcohol: Equilibria and Effect of Temperature

Abstract: Reactive extractions of acrylic, propionic, and butyric acids using Aliquat 336 in oleyl alcohol were carried out to study the effects of temperature (305-333 K). The effects of temperature on the partition (P) and dimerization (D) coefficients were evaluated, and it was found that P decreases with increasing temperature, whereas the effects of temperature on D vary. Chemical extractions using Aliquat 336 in oleyl alcohol at temperatures ranging from 305 to 333 K show an increase in K E(1:1) values with temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 22 publications
2
73
0
Order By: Relevance
“…Similar observations have been made by many researchers. 33,34 Therefore, it is concluded that lower temperature and pH with higher C TBP favour the extraction efficiency. Optimization of process variables C GA0 , C TBP , T, and pH 0 was performed using the numerical optimization method to achieve optimal conditions to maximize the extraction.…”
Section: Response Surface Analysis Process Optimization and Validationmentioning
confidence: 99%
“…Similar observations have been made by many researchers. 33,34 Therefore, it is concluded that lower temperature and pH with higher C TBP favour the extraction efficiency. Optimization of process variables C GA0 , C TBP , T, and pH 0 was performed using the numerical optimization method to achieve optimal conditions to maximize the extraction.…”
Section: Response Surface Analysis Process Optimization and Validationmentioning
confidence: 99%
“…Therefore, it is important to study the effect of temperature on the reactive extraction. Many researchers have studied the influence of temperature on % E and reported that the extractability decreases with increasing temperature …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the IR data also support the proposed reaction scheme. Keshav et al [11] and Zhenyu et al [12] also suggest such complexation mechanism in their study of extraction of propionic acid and P-aminobenzenesulfonic acid, respectively, by QCl.…”
Section: Mechanistic Considerationmentioning
confidence: 93%